The adequacy of the Town & Country Planning Act 1976(Act 172) Towards sustainable development : a case study in the city of Shah Alam / Nani Mawarni Mohd Rasmi … [et al.] - Mohd Rasmi, Nani Mawarni; Ab. Hafidz, Intan Idzadja Hidayah; Muhamad Radzi, Nor Fatihah; Yahaya, Zainab Aljahsyi (2010)
Sustainable development is a process that is not scientifically defined capacity; it describes the journey that we must undertake in order to arrive the destination. Sustainable; involves political and economic processes, not by science and imperial data, but in such a way as to mean almost anything that everybody wants it to mean. In achieving sustainable development, more trees are needed. Therefore there will be increased number of "green areas" and contributes to a better environment. The federal government had responsible Department of Town and Country Planning together with National Land Department in supervising and maintaining all the effort and action that planned to done. Town & Country Planning Act 1976 (Act 172) is the fundamental reference that should be referred to, regarding the town planning. It is unreliable that every statute had been enforce should be followed but however, still, there is some defects that should be monitored by Ministry of Energy Green Technology and Water of Malaysia. In this paper, it will discuss the need of the specific landscaping law to be applied in every state in Malaysia. However the limitation of this project paper is to review the extension and the application of the Section 21 (3) (g) of Town Country & Planning Act1976 towards the penalty which will be given to developer who fails to perform the law.